2018
DOI: 10.18521/ktd.356832
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Privacy in the Emergency Department: Medical Faculty Hospital as A Case in Point

Abstract: Objective: Patient privacy is a complex concept that may be affected by many parameters in healthcare services, especially in Emergency (ER) Departments. To examine the privacy of patients receiving healthcare and medical treatment in the ED, and to evaluate privacy-related problems, if any, from the ethical perspective. Methods: The data-collecting instrument in this study was a survey form consisting of 11 questions seeking demographic information about participants and 15 privacy-related questions formulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Earlier research stated that privacy during hospitalization can be endangered because the setting is often intimate [ 43 ]. Ozturk [ 44 ] explained that privacy protection is closely related to patients’ trust in HCPs [ 44 ]. Additionally, Rojas showed that HCPs usually defend the privacy in terms of the identity of the patients, while they neglect the feelings and thoughts a patient might have [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research stated that privacy during hospitalization can be endangered because the setting is often intimate [ 43 ]. Ozturk [ 44 ] explained that privacy protection is closely related to patients’ trust in HCPs [ 44 ]. Additionally, Rojas showed that HCPs usually defend the privacy in terms of the identity of the patients, while they neglect the feelings and thoughts a patient might have [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It emphasized in some studies that the importance of increasing women's awareness of breast cancer, teaching self-breast examination, promoting women with speciallyprepared reminders and trainings based on model on women's regular mammography (19)(20). Ozturk H et al stated in their work that patient privacy was a complex concept that might be affected by many conditions in healthcare services (21). Women give more importance to privacy from men.…”
Section: Discussionmentioning
confidence: 99%
“…The scores ranged between 21 and 63, while a higher score indicated more positive attitude. The overall score was divided into three levels of negative (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), moderate (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), and positive attitude (50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). The scoring of the third to seventeenth questions was done inversely.…”
Section: Methodsmentioning
confidence: 99%
“…Female patients were more sensitive than males to observance of the physical dimension, avoidance of unnecessary touches, and maintenance of privacy. 46,47 Receiving care from a nurse of the opposite gender increased the possibility of violating patient privacy. 38 Therefore, special measures should be adopted to provide at least patient private care by a nurse of the same gender.…”
Section: Duman's Study In Turkey and Walton Et Al's Study On Americanmentioning
confidence: 99%